In vitro effect of seven essential oils on the reproduction of the cattle tick Rhipicephalus microplus - Pazinato R.* (2016)
© 2016The acaricidal effect of seven essential oils was examined in vitro against the cattle tick (Rhipicephalus microplus). Engorged female ticks were manually collected in farms of Southern Brazil and placed into petri dishes (n = 10) in order to test the following oils: juniper (Juniperus communis), palmarosa (Cymbopogon martinii), cedar (Cedrus atlantica), lemon grass (Cymbopogon citratus), ginger (Zingiber officinale), geranium (Pelargonium graveolens) and bergamot (Citrus aurantium var bergamia) at concentrations of 1%, 5%, and 10% each. A control group was used to validate the tests containing Triton X-100 only. Treatment effectiveness was measured considering inhibition of tick oviposition (partial or total), egg's weight, and hatchability. C. martinii, C. citratus and C. atlantica essential oils showed efficacy higher than 99% at all concentrations tested. In addition, J. communis, Z. officinale, P. graveolens, and C. aurantium var bergamia oils showed efficiency ranging from 73% to 95%, depending on the concentration tested, where higher concentrations showed greater efficacy. It was concluded that essential oils can affect tick reproduction in vitro by inhibiting oviposition and hatchability.